2010
DOI: 10.1037/a0016494
|View full text |Cite
|
Sign up to set email alerts
|

A dimensional analysis of creativity and mental illness: Do anxiety and depression symptoms predict creative cognition, creative accomplishments, and creative self-concepts?

Abstract: . (in press). A dimensional analysis of creativity and mental illness: Do anxiety and depression symptoms predict creative cognition, creative accomplishments, and creative self-concepts? Psychology of Aesthetics, Creativity, and the Arts. Abstract:The link, if any, between creativity and mental illness is one of the most controversial topics in modern creativity research. The present research assessed the relationships between anxiety and depression symptom dimensions and several facets of creativity: diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 78 publications
(97 reference statements)
4
73
0
4
Order By: Relevance
“…As for the remaining factors, (i.e., Conscientiousness, Neuroticism, and Agreeableness) the results have been more ambiguous and complex Reiter-Palmon, Illies, & Kobe, 2009;Silvia & Kimbrel, 2010).It has been found that Neuroticism is a positive predictor of artistic creativity but a negative predictor of scientific and daily creativity (Batey & Furnham, 2006) as well as divergent thinking (Chamorro-Premuzic & Reichenbacher, 2008). Finally, Batey, Chamorro-Premuzic, and Furnham (2010) specifically found that the facet vulnerability of Neuroticism was a negative predictor of ideational behavior.…”
Section: Personality and Creativity In Adultsmentioning
confidence: 99%
“…As for the remaining factors, (i.e., Conscientiousness, Neuroticism, and Agreeableness) the results have been more ambiguous and complex Reiter-Palmon, Illies, & Kobe, 2009;Silvia & Kimbrel, 2010).It has been found that Neuroticism is a positive predictor of artistic creativity but a negative predictor of scientific and daily creativity (Batey & Furnham, 2006) as well as divergent thinking (Chamorro-Premuzic & Reichenbacher, 2008). Finally, Batey, Chamorro-Premuzic, and Furnham (2010) specifically found that the facet vulnerability of Neuroticism was a negative predictor of ideational behavior.…”
Section: Personality and Creativity In Adultsmentioning
confidence: 99%
“…We assessed creativity with three self-report measures of creative achievement and activity that have performed well in our past work (Silvia andKimbrel, 2010 and and that have been recommended in a recent review of creativity assessment (Silvia, Wigert, ReiterPalmon, & Kaufman, in press). The Creative Behavior Inventory (CBI; Dollinger, 2007) is a 28-item scale that asks people to report how often they have done various creative acts, with an emphasis on the visual and performing arts, writing, and crafts.…”
Section: Methodsmentioning
confidence: 99%
“…For divergent thinking tasks, several trained raters simply evaluate and score individual ideas (Silvia, 2011, Silvia and Kimbrel, 2010 or the set of ideas ). Thus far, we have found that subjective ratings of creativity are unconfounded with fluency and that the relationships of creativity with intelligence are substantially larger (Nusbaum & Silvia, 2011a).…”
mentioning
confidence: 99%